On the Causative Strokes of Halos Observed by ISUAL in the Vicinity of North America. Issue 19 (13th October 2018) - Lu, Gaopeng; Yu, Bingkun; Cummer, Steven A.; Peng, Kang‐Ming; Chen, Alfred B.; Lyu, Fanchao; Xue, Xianghui; Liu, Fei; Hsu, Rue‐Ron; Su, Han‐Tzong
Abstract: The analysis of impulse charge moment change (iCMC) for the parent lightning strokes of 497 halos observed by the Imager of Sprites and Upper Atmospheric Lightning near North America in 2004–2015 indicates that the majority were produced by negative cloud‐to‐ground strokes predominantly produced in oceanic and coastal thunderstorms. Positive halos are almost always accompanied by sprites, and negative sprites are usually associated with halos. There are limited observations of positive pure halos with supercritical iCMCs (> +320 C km), but there are many negative pure halos with supercritical iCMCs (> −500 C km), suggesting a critical role of impulse charge transfer duration in the formation of streamers. The halo‐producing threshold of lightning strength does not considerably depend on the polarity. Due to the dependence on the timescale of impulse charge transfer for streamer development, many negative cloud‐to‐ground strokes with iCMCs exceeding the threshold for sprite production actually produce halos instead. Plain Language Summary: Our previous analysis has shown some features for the parent lightning strokes of red sprites observed by the Imager of Sprites and Upper Atmospheric Lightning in the vicinity of North America during a 12‐year period from 2004 to 2015. In this paper, we extend the analysis to 497 halos observed by Imager of Sprites and Upper Atmospheric Lightning in the same region and during the same time period. The results show that the majority (75%) of halos were produced by negative cloud‐to‐ground strokes, which are predominantly produced in oceanic thunderstorms. The duration of impulse charge transfer plays a critical role in the formation of sprite streamers. There are only very limited observations of positive pure halos with supercritical iCMCs (> +320 C km) for positive sprites, whereas there are many negative pure halos with supercritical iCMCs (> −500 C km) for negative sprites. Due to the dependence on the timescale of impulse charge transfer for the streamer development, many negative cloud‐to‐ground strokes with impulse charge transfer exceeding the threshold for sprite production actually produce halos instead. Key Points: The vast majority of halos observed by ISUAL are produced by negative cloud‐to‐ground strokes predominantly over oceans The production of halo and sprite observed by ISUAL is dominated by negative and positive cloud‐to‐ground strokes, respectively Threshold of lightning in terms of impulse charge moment change for halo production does not exhibit a dependence on lightning polarity